(untitled) (Eurasian Medical Research Periodical, 2022)
The main criterion is the constancy of the teeth. The inconsistency of these parameters can lead to the appearance of gaps between the teeth. This article presents data on the structural features of the dentition and facial skeleton, as well as data on the preservation or removal of teeth when planning orthodontic treatment. Based on the study of patient data, it is necessary to study the biometric structural features of the dentition with angeries of the first and second Engel occuli in patients who need tooth extraction before orthodontic treatment, to conduct a comparative analysis of biometric and X-ray cephalometric indices with anomalies of the bite of the first and second Engle classes.